Depth-resolved band alignments of perovskite solar cells with significant interfacial effects. Issue 6 (16th January 2017) - Eom, Kiryung; Kwon, Uisik; Kalanur, Shankara S.; Park, Hui Joon; Seo, Hyungtak
Abstract : The band alignment in heterojunction solar cells, including perovskite solar cells (PSCs), is critically related to power conversion efficiency (PCE) improvement as it has a significant effect on the control of photocarrier transport. Abstract : The band alignment in heterojunction solar cells, including perovskite solar cells (PSCs), is critically related to power conversion efficiency (PCE) improvement as it has a significant effect on the control of photocarrier transport. In the present study, in an attempt to identify the correlation between the energy band structure of PSCs and their PCEs, we analyzed the energy-band structures of both p–i–n type and n–i–p type PSC devices, especially those having the most widely utilized planar and mesoporous (mp) structures, by using spectroscopic approaches. Two types (planar and mp) of perovskite solar cells were fabricated. The PCEs were measured and found to be 12.5% for the planar structure and 14.7% for the mp structure. To investigate the physicochemical origin of such PCE differences depending on the cell type, comprehensive band alignment and band structure analyses at the actual cell stacks were performed using UV-vis and XPS depth measurements. Both planar and mp structures showed negative conduction band offset (CBO) for the efficient electron transfer and positive valence band offset for hole transfer. Especially, the perovskite/mp-TiO2 interface with a negative CBO has a widely distributed 3-dimensional junction with a graded electronic band structure. In the present study, we identify the electron transport mechanism and its relevance to the band alignment and its effect on PCE by comparing two different perovskite solar cell structures and, furthermore, examine the unique junction formation caused by the mp-TiO2 nanostructure.